The intergenerational relationship between conditional cash transfers and newborn health - Andreza Daniela Pontes Lucas; Monaliza de Oliveira Ferreira; Tarcisio Daniel Pontes Lucas; Paola Salari (BMC, 2022)
Abstract Background Lack of nutrition, inadequate housing, low education and limited access to quality care can negatively affect children's health over their lifetime. Implemented in 2003, the Bolsa Familia ("Family Stipend") Program (PBF) is a conditional cash transfer program targeting poor households in Brazil. This study investigates the long-term benefits of cash transfers through intergenerational transmission of health and poverty by assessing the early life exposure of the mother to the PBF. Methods We used data from the 100M SINASC-SIM cohort compiled and managed by the Center for Data and Knowledge Integration for Health (CIDACS), containing information about participation in the PBF and socioeconomic and health indicators. We analyzed five measures of newborn health: low (less than 2,500 g) and very low (less than 1,500 g) birth weight, premature (less than 37 weeks of gestation) and very premature (less than 28 weeks of gestation) birth, and the presence of some type of malformation (according to ICD-10 codes). Furthermore, we measured the early life exposure to the PBF of the mother as PBF coverage in the previous decade in the city where the mother was born. We applied multilevel logistic regression models to assess the associations between birth outcomes and PBF exposures. Results Results showed that children born in a household where the mother received BF were less likely to have low birth weight (OR 0.93, CI; 0.92-0.94), very low birth weight (0.87, CI; 0.84-0.89), as well as to be born after 37 weeks of gestation (OR 0.98, CI; 0.97-0.99) or 28 weeks of gestation (OR 0.93, CI; 0.88-0.97). There were no significant associations between households where the mother received BF and congenital malformation. On average, the higher the early life exposure to the PBF of the mother, the lower was the prevalence of low birth weight, very low birth weight and congenital malformation of the newborn. No trend was noted for preterm birth. Conclusion The PBF might have indirect intergenerational effects on children's health. These results provide important implications for policymakers who have to decide how to effectively allocate resources to improve child health.